Compassion and empathy in palliative care for end-of-life patients - Cardoso, Ariel Gayo Carvalho; Souza, Janayna Pereira de; Santos, Maria Eduarda Pereira dos; Sales, Sarah Myrelle Santos; Menezes, Mariana Rodrigues da Silva de (Seven Editora, 2024)
Introduction: Compassion and empathy are considered an essential complement to palliative care. Professionals in the field seek to promote, investigate, and understand compassion and empathy as a fundamental part of care practice. Objective: To identify and synthesize articles that address compassion and empathy in palliative care of patients at the end of life. Methodology: Integrative literature review. The databases Medline, Pubmed, Lilacs, Bdenf, Ibesc, Binacis, Wprim were used. Descriptors used for online search: Bioethics, Palliative Care, Empathy and Compassion. Results: A total of forty-one articles were obtained, which after application of the exclusion criteria, resulted in four articles that explored the challenges that health professionals face when dealing with Palliative Care with patients at the end of life. Discussion: In the final moments of life, compassion aims to help patients relieve their symptoms, since there is no possibility of complete cure. Conclusion: Effective communication, compassion, and empathy in the provision of palliative care are essential to improve quality of life for patients and their families. DOI:https://doi.org/10.56238/sevened2023.006-133